دراسة أثر الإبداع الإداري على الأداء الوظيفي للعاملين في المركب المنجمي للفوسفات بجبل العنق بتبسة - خالد, علي (جامعة الوادي - University of Eloued, 2017)
يركز هذا البحث على دراسة أثر الإبداع الإداري على الأداء الوظيفي للعاملين في المركب المنجمي للفوسفات بجبل العنق. وقد اعتمدت الدراسة على استبانه وزعت على عينة من العاملين في المركب، تكونت من شقين: الأول يشير إلى البيانات الشخصية للمبحوثين، أما الشق الثاني فتضمن أربعة محاور تتعلق بالموضوع المدروس. وخلصت الدراسة إلى أن مستوى الإبداع الإداري في المركب وكذلك مستوى الأداء الوظيفي كانا مرتفعين إلى حد ما، في حين أن إدارة المركب لا تتبع الأساليب الإدارية التي تدعم الإبداع وتعززه لدى العاملين بما يحقق مستوى أداء متميز وفعال. الأمر الذي جعل عجلة التنمية داخل المركب تراوح مكانها، على الرغم مما يمتلكه هذا الأخير من إمكانيات مادية وبشرية تأهله للصدارة محليا وعالميا. This study focuses on the impact of administrative creativity on functionality for the workers in the mining of Phosphates in «Djebel Onk». The study was based on a questionnaire, distributed to a sample of workers in the compound, which consisted of two parts: the first, refers to the personal data of respondents, while the second part has four themes related to the subject studied. The study concluded that creativity in the administrative level in the compound, as well as the level of job performance, were high level somewhat.While the compound administration, does not follow the administrative methods, that support innovation and promote the employees, to achieve the level of outstanding performance and effectively. Which made the wheel of development inside the compound at a standstill, though, which is owned by the latter of the potential physical and human qualify for the top spot domestically and internationally.
مقال
Keywords: الإبداع الإداري، الأداء الوظيفي، العاملين ، المركب المنجمي.; Managing creativity, functionality, workers, the mining complex